Small molecule inhibition of ubiquitin C-terminal hydrolase L1 alters cell metabolism proteins and exerts anti- or pro-tumorigenic effects contingent upon chemosensitivity status in high grade serous ovarian cancer - Jansen, Corinne; McAdams, Julia; Kim, Chloe; De La Cruz, Payton; Salaverria, Angelica; DaSilva, Nicholas A.; Grive, Kathryn; James, Nicole E. (Frontiers in Pharmacology, 2025)
High grade serous ovarian cancer (HGSOC) is the most lethal of all gynecologic malignancies in which the majority of patients eventually develop chemoresistant recurrent disease. Ubiquitin C-terminal hydrolase L1 (UCHL1) is a deubiquitinating enzyme canonically known for its involvement in neurodegeneration, but recently has been shown to play a key role in tumorigenesis. Furthermore, UCHL1 has garnered attention across a multitude of cancer subtypes as it has the ability to be targeted through small molecule inhibition. Therefore, the goal of this present study was to elucidate mechanistic consequences of small molecule UCHL1 inhibition in HGSOC. Comparative label-free proteomic analysis of HGSOC cell line, OVCAR8 revealed prominent changes in cell metabolism proteins upon treatment with UCHL1 small molecule inhibitor, LDN-57444. Further validation via Western blot analysis revealed that changes in cell metabolism proteins differed in matched chemosensitive versus chemoresistant HGSOC cells. Finally, cell viability analysis demonstrated that a combinatorial carboplatin and LDN-57444 blockade produced a promotion or conversely, inhibition of cell death, in chemoresistant, and chemosensitve HGSOC cells, respectively. This phenomenon was further corroborated by respective differences in activation levels of common tumor cell growth pathways STAT3, MAPK/ERK, and AKT in chemoresistant versus chemosensitive HGSOC cells. Overall, this investigation established that pharmacologic targeting of UCHL1 produces differential effects according to HGSOC chemosensitivity status.